A preparation method of high-stability thermo-induced flexible phase change material and a shock-absorbing battery module

By adding styrene-butadiene-styrene block copolymer, ethylene propylene ternary rubber and thermal conductivity enhancer to the phase change material, the high stability of thermal induced flexible phase change material is solved, and the existing phase change materials have poor uniformity, poor thermal conductivity and easy leakage at high temperatures are achieved, and the efficient thermal management and vibration buffering effect of the battery module are achieved.

CN113136176BActive Publication Date: 2025-04-25GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110552054.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-20
Publication Date
2025-04-25
Estimated Expiration
2041-05-20

AI Technical Summary

Technical Problem

Existing phase change materials have poor uniformity, poor thermal conductivity, and are prone to leakage when used at high temperatures, which cannot effectively protect the battery module from damage caused by external force impact, collision and vibration.

Method used

High stability thermally flexible phase change material is prepared by melting and mixing the phase change substrate, styrene-butadiene-styrene block copolymer, ethylene propylene ternary rubber and thermal reinforcement under stirring to improve its uniformity and thermal conductivity, and avoid the problem of disconnecting thermal contact with the battery during leakage and vibration.

Benefits of technology

It realizes the high-quality retention rate of phase change materials for long-term use at high temperatures, adapts to battery thermal management needs, improves the lightweight and compactness of the battery module, and effectively avoids thermal contact problems caused by leakage and vibration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003075858340000011
    Figure HDA0003075858340000011
  • Figure HDA0003075858340000012
    Figure HDA0003075858340000012
  • Figure HDA0003075858340000021
    Figure HDA0003075858340000021
Patent Text Reader

Abstract

The present application belongs to the technical field of phase change materials. The present application provides a preparation method of a highly stable thermo-flexible phase change material and a shock-absorbing battery module. The highly stable thermo-flexible phase change material is prepared by melting and mixing a phase change substrate, a styrene-butadiene-styrene block copolymer, ethylene propylene diene rubber and a thermal conductivity enhancer under stirring. By adding ethylene propylene diene rubber (ethylene, propylene and non-conjugated diene copolymer), the crosslinking of the styrene-butadiene-styrene block copolymer can be effectively increased, and its adsorption to the phase change substrate can be increased, and the phenomenon of phase separation between the styrene-butadiene-styrene block copolymer and the phase change substrate can be effectively avoided, thereby improving the uniformity of the phase change material, so that the phase change material still has a high quality retention rate when used for a long time at high temperature, and can achieve lightweight and compactness of the battery module, improve the thermal conductivity of the phase change material, and effectively avoid the problem of thermal contact with the battery during leakage and vibration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of phase change materials, and in particular, relates to a method for preparing a high-stability thermo-flexible phase change material and a shock-absorbing battery module. Background Art

[0002] In recent years, due to the energy shortage crisis, environmental pollution and greenhouse effect caused by the continuous consumption of fossil energy, the development and utilization of sustainable green energy has become an important focus of sustainable development. Electric vehicles using green and clean energy can effectively reduce the consumption of fossil energy and greenhouse gas emissions of traditional fuel vehicles. Among them, the performance and safety of power batteries as energy supply components of electric vehicles directly affect the performance and safety of electric vehicles, and even the safety of drivers. In actual use, power battery systems often need to experience different working conditions, such as high temperature, long-term use, high-rate discharge use, etc. These use conditions are accompanied by a large amount of heat generation. When the heat of the battery cannot be transferred in time, it will cause battery performance degradation or even thermal runaway. When electric vehicles are frequently vibrated or collided, the battery cannot be protected accordingly and is very likely to explode. Therefore, the power battery system requires an effective battery thermal management system, which can not only ensure the normal operating temperature of the battery module, but also protect the battery from external factors such as impact, collision and vibration.

[0003] At present, the mainstream battery thermal management methods include air cooling, liquid cooling and phase change material cooling. As active cooling methods, air cooling and liquid cooling not only consume extra energy to achieve heat dissipation protection for the battery during use, but also cannot effectively protect the battery system from damage caused by external forces such as impact, collision and vibration. Phase change materials face problems such as poor uniformity, poor thermal conductivity and easy leakage. Summary of the invention

[0004] In view of this, the present application provides a method for preparing a high-stability thermoflexible phase change material and a shock-absorbing battery module, which are used to solve the technical problems of poor uniformity, poor thermal conductivity and easy leakage of phase change materials.

[0005] The specific technical solutions of this application are as follows:

[0006] The present application provides a method for preparing a high-stability thermo-flexible phase change material, comprising the following steps:

[0007] S1: Melting the phase change substrate, adding styrene-butadiene-styrene block copolymer and stirring to dissolve, to obtain a translucent colloidal solution;

[0008] S2: adding EPDM rubber to the translucent colloidal solution and stirring and melting the mixture to obtain a viscous colloidal solution;

[0009] S3: adding a thermal conductivity enhancer to the viscous colloidal solution, stirring and mixing, and pouring the solution into a mold for curing to obtain the high-stability thermo-flexible phase change material.

[0010] In the present application, by adding EPDM rubber (a copolymer of ethylene, propylene and non-conjugated dienes), the crosslinking of styrene-butadiene-styrene block copolymer can be effectively increased, and its adsorption to the phase change substrate can be increased, thereby effectively avoiding the phase separation of styrene-butadiene-styrene block copolymer and the phase change substrate, thereby improving the uniformity of the phase change material, so that the phase change material still has a high quality retention rate after long-term use at high temperature, which can achieve lightweight and compactness of the battery module and improve the thermal conductivity of the phase change material.

[0011] Styrene-butadiene-styrene block copolymer can form a flexible support skeleton and provide good flexibility for the phase change material; adding a thermal conductivity enhancer can effectively improve the thermal conductivity of the phase change material, thereby more effectively adapting to battery thermal management. The high-stability thermally induced flexible phase change material prepared by this preparation method has a phase change temperature range of 45-50°C, a high thermal conductivity, and effectively avoids the problem of thermal contact with the battery during leakage and vibration.

[0012] Preferably, the mass ratio of the phase change substrate, the styrene-butadiene-styrene block copolymer and the EPDM rubber is 8:(1-1.7):(0.3-0.7).

[0013] Preferably, the added amount of the thermal conductivity enhancer is 3-5wt% of the total mass.

[0014] Preferably, the melting temperature in S1 is 140-150° C., and the stirring and dissolving speed is 300-500 rad / min.

[0015] Preferably, the rotation speed of the stirring and mixing in S2 and S3 is 800-1000 rad / min.

[0016] Preferably, the phase change substrate is selected from paraffin and / or polyethylene glycol, and the thermal conductivity enhancer is selected from expanded graphite, graphene and / or carbon nanotubes.

[0017] The present application also provides a shock absorbing battery module, including a box body and a battery bracket;

[0018] The battery holder is placed in the box and is used to load batteries;

[0019] The battery bracket is made of a high-stability thermo-flexible phase change material obtained by the preparation method.

[0020] Preferably, the battery holder comprises a loading tube and a connecting piece connecting the loading tubes in series at intervals;

[0021] The loading cylinder is provided with a loading hole for the battery to extend into, and the loading hole is interference fit with the battery.

[0022] Preferably, the loading cylinder, the connecting member and the battery are of the same height.

[0023] Preferably, the connecting members are linear and are arranged at intervals along the length direction of the box body, so that the loading cylinders on adjacent connecting members are spaced apart.

[0024] Preferably, the length of the connecting piece is adapted to the box body.

[0025] Preferably, the thickness of the connecting member is 3-5 mm, the thickness of the loading tube is 3-5 mm, the spacing distance between the loading tubes is 7-11 mm, and the spacing distance between the loading tubes on adjacent connecting members is 3-5 mm.

[0026] Preferably, the number of the loading cylinders connected in series on the connecting piece is 3 to 5.

[0027] Preferably, the battery holder is connected to the box body via a snap fastener.

[0028] In summary, the present application provides a preparation method of a high-stability thermo-flexible phase change material and a shock-absorbing battery module. The high-stability thermo-flexible phase change material is prepared by melting and mixing a phase change substrate, a styrene-butadiene-styrene block copolymer, ethylene propylene diene monomer rubber and a thermal conductivity enhancer under stirring. By adding ethylene propylene diene monomer rubber (ethylene, propylene and non-conjugated diene copolymer), the cross-linking of the styrene-butadiene-styrene block copolymer can be effectively increased, and its adsorption to the phase change substrate can be increased, and the phase separation of the styrene-butadiene-styrene block copolymer and the phase change substrate can be effectively avoided, thereby improving the uniformity of the phase change material, so that the phase change material still has a high quality retention rate when used for a long time at high temperature, and can achieve lightweight and compactness of the battery module, improve the thermal conductivity of the phase change material, and effectively avoid the problem of thermal contact with the battery during leakage and vibration. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0030] Figure 1 This is a graph showing the quality retention performance results of the product obtained in the embodiment of the present application after continuous heating;

[0031] Figure 2 This is a graph showing the thermal conductivity of the product obtained in the present embodiment;

[0032] Figure 3 A schematic diagram of the structure of a battery module provided in an embodiment of the present application;

[0033] Figure 4 A top view of a battery module provided in an embodiment of the present application;

[0034] Illustrations: 1. Box body; 2. Loading cylinder; 3. Loading hole; 4. Connector; 5. Battery. DETAILED DESCRIPTION

[0035] In order to make the purpose, features, and advantages of this application more obvious and easy to understand, the technical solutions in the embodiments of this application are clearly and completely described. Obviously, the embodiments described below are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] Example 1

[0037] (1) melting paraffin at 150° C., adding styrene-butadiene-styrene block copolymer and stirring at 500 rad / min to dissolve the mixture, and obtaining a translucent colloidal solution;

[0038] (2) adding ethylene propylene diene monomer (ethylene, propylene and non-conjugated diene terpolymer, molecular weight distribution: 2-5) to the translucent colloidal solution and stirring and melting at 1000 rad / min, wherein the mass ratio of paraffin wax, styrene-butadiene-styrene block copolymer and ethylene propylene diene monomer is 8:1:0.5, to obtain a viscous colloidal solution;

[0039] (3) Adding expanded graphite to the viscous colloidal solution and stirring and mixing at 1000 rad / min, wherein the addition amount of the thermal conductivity enhancer is 1wt%, 3wt% and 5wt% of the total mass, respectively, and pouring into a mold for curing to obtain products E-SPEG1, E-SPEG3 and E-SPEG5, respectively.

[0040] Comparative Example 1

[0041] The paraffin wax was melted at 150° C., and styrene-butadiene-styrene block copolymer was added and stirred and dissolved at 500 rad / min, wherein the mass ratio of the paraffin wax to the styrene-butadiene-styrene block copolymer was 8:1.5. The paraffin wax was poured into a mold for solidification to obtain a product SP.

[0042] Comparative Example 2

[0043] (1) melting paraffin at 150° C., adding styrene-butadiene-styrene block copolymer and stirring at 500 rad / min to dissolve the mixture, and obtaining a translucent colloidal solution;

[0044] (2) Add EPDM rubber to the translucent colloidal solution and stir and melt at 1000 rad / min, wherein the mass ratio of paraffin wax, styrene-butadiene-styrene block copolymer and EPDM rubber is 8:1:0.5 (the amount of EPDM rubber added is 3wt% of the total mass), to obtain a viscous colloidal solution, which is poured into a mold for solidification to obtain product E-SP3. Using the same preparation method, the amount of EPDM rubber added is adjusted to 1wt% and 5wt% of the total mass to obtain products E-SP1 and E-SP5.

[0045] Comparative Example 3

[0046] (1) Melting paraffin at 70° C., adding epoxy resin (condensation product of epichlorohydrin and bisphenol A) and stirring at 500 rad / min to uniformly mix the epoxy resin and liquid paraffin;

[0047] (2) adding expanded graphite (expansion ratio: 500) to paraffin wax / epoxy resin, maintaining the mixture at 70° C. and stirring at 1000 rad / min, wherein the mass ratio of paraffin wax, epoxy resin and expanded graphite is 8:0.75:0.5, to obtain a uniform mixed solution;

[0048] (3) Add a curing agent (polyurethane adhesive) to the uniformly mixed solution and stir at 1000 rad / min, wherein the mass of the curing agent is the same as that of the epoxy resin, accounting for 7.5wt% of the total mass ratio. After stirring for 10 minutes, pour it into a mold for curing to obtain the product Er-PCM.

[0049] Figure 1The quality retention performance result diagram of the product obtained by the embodiment of the present application after continuous heating shows that when the product (SP) obtained by comparative example 1 is continuously heated at 60°C, obvious leakage of phase change components will occur after 3 hours, and after 10 hours of continuous heating, the quality retention rate is only about 95%. The quality retention rate of the product (E-SP3) obtained by comparative example 2, which adds ethylene propylene diene monomer rubber (EPDM) on the basis of comparative example 1, can still be maintained at more than 99% after 10 hours of heating, and at the same time, there is no obvious leakage of phase change components. However, the quality retention rate of the product (E-SPEG5) obtained by the embodiment of the present application is improved by adding expanded graphite (EG), and the retention rate after 10 hours of heating is about 100%. In addition, the quality retention rate (96.8%) of the product (Er-PCM) of comparative example 3 after heating for 10 hours is significantly lower than that of the product of the embodiment of the present application 1.

[0050] Figure 2 The thermal conductivity result diagram of the products obtained in the examples of the present application shows that the thermal conductivity of the product (SP) obtained in comparative example 1 and the products E-SP1, E-SP3 and E-SP5 of comparative example 2, in which the addition amount of EPDM rubber is 1wt%, 3wt% and 5wt% of the total mass respectively, are all lower than 0.3W / (m·K). The thermal conductivity of the products E-SPEG1, E-SPEG3 and E-SPEG5 obtained in Example 1 is distributed in the range of 0.4 to 1.2W / (m·K), and the thermal conductivity is significantly improved, especially the thermal conductivity of the product E-SPEG5 is comparable to that of the product Er-PCM of comparative example 3.

[0051] Example 2

[0052] Please refer to Figures 3-4 The embodiment of the present application provides a shock-absorbing battery 5 module, including a box body 1 and a battery holder; the battery holder is placed in the box body 1 and is used to load the battery 5; the battery holder is made of the product obtained in Example 1.

[0053] In the embodiment of the present application, the phase change material has good flexibility and still has a high quality retention rate when used for a long time at high temperature, which can achieve the lightweight and compactness of the battery 5 module, and improve the thermal conductivity of the phase change material, more effectively adapt to the thermal management of the battery 5, and avoid the problem of thermal contact with the battery 5 during leakage and vibration. It should be noted that the box 1 is made of insulating material.

[0054] Furthermore, the battery holder includes a loading tube 2 and a connector 4 that connects the loading tubes 2 in series at intervals; the loading tube 2 is provided with a loading hole 3 for the battery 5 to extend into, and the loading hole 3 and the battery 5 are interference fit.

[0055] In the embodiment of the present application, the loading cylinders 2 on the battery holder are connected in series and spaced apart through the connector 4, which can effectively improve the stability of the supported battery 5 and cushion the impact of vibration on the battery 5; at the same time, such a structural design facilitates secondary heat dissipation coupling with air cooling or liquid cooling, thereby optimizing the heat dissipation of the battery 5 module and improving the heat absorption / release efficiency.

[0056] Furthermore, the heights of the loading cylinder 2 , the connecting member 4 and the battery 5 are the same.

[0057] In the embodiment of the present application, the loading cylinder 2 can stably fix the battery 5, and the connecting member 4 can effectively disperse the heat and improve the heat transfer efficiency.

[0058] Furthermore, the connecting members 4 are linear and are arranged at intervals along the length direction of the box body 1 so that the loading cylinders 2 on adjacent connecting members 4 are spaced apart.

[0059] In the embodiment of the present application, under the fixing effect of the connecting member 4, the loading tubes 2 on adjacent connecting members 4 are arranged at intervals, which can not only ensure the stability of the loading of the battery 5, but also improve the heat dissipation effect of the battery 5 module.

[0060] Furthermore, the length of the connecting member 4 is adapted to the box body 1 .

[0061] In the embodiment of the present application, the two ends of the connector 4 just butt against the inner wall of the box body 1, thereby increasing the stability of the battery 5 loading and avoiding thermal contact with the battery 5 during vibration.

[0062] Furthermore, the thickness of the connecting member 4 is 3 mm, the thickness of the loading tube 2 is 5 mm, the spacing distance between the loading tubes 2 is 5 mm, and the spacing distance between the loading tubes 2 on adjacent connecting members 4 is 11 mm.

[0063] In the embodiment of the present application, the structural design can meet the heat dissipation requirements and thermal conductivity of the battery 5 module, and can also make full use of the space to achieve stability and leakage prevention.

[0064] Furthermore, the number of loading cylinders 2 connected in series on the connecting member 4 is three.

[0065] In the embodiment of the present application, the number of loading tubes 2 connected in series on the connecting member 4 should not be too large, which will lead to an unstable assembly structure and easily cause the loading tubes 2 to be misplaced and out of thermal contact.

[0066] Furthermore, the battery holder is connected to the box body 1 via a snap fastener.

[0067] In the embodiment of the present application, a buckle may be provided at the bottom of the battery bracket, which is engaged with the limiting groove at the bottom of the box body 1 to enhance the fixing effect of the battery 5.

[0068] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A shock absorbing battery module, characterized in that: Including box and battery holder; The battery holder is placed in the box and is used to load the battery; the battery holder is made of a high-stability thermo-flexible phase change material; The battery holder comprises a loading tube and a connecting piece connecting the loading tubes in series at intervals; The loading cylinder is provided with a loading hole for the battery to be inserted into, and the loading hole is interference fit with the battery; The connecting members are linear and arranged at intervals along the length direction of the box body, so that the loading cylinders on adjacent connecting members are spaced apart; The method for preparing the high-stability thermo-flexible phase change material comprises the following steps: S1: Melting the phase change substrate, adding styrene-butadiene-styrene block copolymer and stirring to dissolve, to obtain a translucent colloidal solution; S2: adding EPDM rubber to the translucent colloidal solution and stirring and melting the mixture to obtain a viscous colloidal solution; S3: adding a thermal conductivity enhancer to the viscous colloidal solution, stirring and mixing, and pouring the solution into a mold for curing to obtain the high-stability thermo-flexible phase change material; The mass ratio of the phase change substrate, the styrene-butadiene-styrene block copolymer and the EPDM rubber is 8: (1-1.7): (0.3-0.7); The phase change substrate is paraffin.

2. The shock absorbing battery module according to claim 1, characterized in that: The amount of the thermal conductivity enhancer added is 3-5wt% of the total mass of the high-stability thermoflexible phase change material.

3. The shock absorbing battery module according to claim 1, characterized in that: The melting temperature in S1 is 140-150° C., and the rotation speed of the stirring and dissolving is 300-500 rad / min.

4. The shock absorbing battery module according to claim 1, characterized in that: The rotation speed of the stirring and mixing in S2 and S3 is 800-1000 rad / min.

5. The shock absorbing battery module according to claim 1, characterized in that: The thermal conductivity enhancer is selected from expanded graphite, graphene and / or carbon nanotubes.

6. The shock absorbing battery module according to claim 1, characterized in that: The loading cylinder, the connecting member and the battery have the same height.

Citation Information

Patent Citations

  • Preparation method of high-thermal-conductivity flexible phase-change material and battery module

    CN111607362A